Community livability : issues and approaches to sustaining the well-being of people and communities - Wagner, Fritz; Caves, Roger W (New York : Routledge, 2012)
What is a livable community? How do you design and develop one? What does government at all levels need to do to support and nuture the cause of livable communities? Using a blend of theory and practice, experts in the field look at evidence from international, state and local perspectives to explore what is meant by the term'livable communities'. Chapters examine the various influencing factors such as the effect and importance of transportation options/alternatives to the elderly, the significance of walkability as a factor in developing a livable and healthy community, the importance of good open space providing for human activity and health, restorative benefits, the importance of coordinated land use and transportation planning, and the relationship between livability and quality of life. While much of the discussion of this topic is usually theoretical and abstract, Wagner and Caves use case studies from North America, Brazil and the United Kingdom to provide substantive examples of initiatives implemented across the world. This book fills an important gap in the literature on livable communities and at the same time assists policy officials, professionals and academics in their quest to develop livable communities.
Section III: Specific Interventions. Public Participation in Neighborhood Planning, A Neglected Aspect of Community Livability: The Case of Seattle / Hilda Blanco. -- Envisioning A City's Green Infrastructure for Community Livability / Nancy D. Rottle and Brice Maryman. -- Does Land Use and Transportation Coordination Really Make a Difference in Creating Livable Communities? / Ruth L. Steiner. -- Livability, Health, and Community Design / Sarah Heaton Kennedy and Andrew L. Dannenberg. -- Final Thoughts on Community Livability / Roger Caves and Fritz Wagner.
Includes bibliographical references and index.
Keywords: Sustainable living -- Case studies; Community life -- Case studies